Uncertain Multiattribute Decision-Making Based on Interval Number with Extension-Dependent Degree and Regret Aversion. (27th August 2018) - Xu, Libo; Li, Xingsen; Pang, Chaoyi
Abstract : In view of the uncertainty multiattribute decision-making problem with attribute values and weights both being interval number, a new solution based on regret theory and extension-dependent degree is proposed. It can define pass value of each attribute, which means decision-maker's acceptance for the scheme under the pass value will decline quickly. Then according to traditional regret theory, the method defines an extension-dependent function based on pass value which can improve the flexibility of the traditional utility function and the ability to describe the risk aversion actions from decision-makers. Then the extension-dependent function for interval number is built, and the perceived utility value of each scheme is obtained based on the interval's optimal value. The method can also reflect the decision-maker's reference to high or low evaluation score by setting attitude coefficients. At last, an example is presented to examine the feasibility, effectiveness, and stability of our method.